International Conference on Space Optics — ICSO 2016 2017
DOI: 10.1117/12.2296209
|View full text |Cite
|
Sign up to set email alerts
|

Caveats and pitfalls of high energy UV laser operation on ground

Abstract: Abstract-During the Aeolus laser and instrument transmitter development it was shown that atmosphere quality was one major limiting factor for high energy UV laser operation at ambient pressure. As already proven in literature operation can only be safely obtained in the presence of oxygen ([1] to [6]).Furthermore, air quality has to be adequately controlled and monitored to ensure that no catastrophic event occurs. On-line qualitative (no/no-go discriminator) can be obtained using fluorescence monitoring of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…This type of laser has the disadvantage of being sensitive to vibrations due to the number of free space optics and the presence of piezo-monitored optics to maintain the laser cavity adapted to the injected wavelength. These challenges have led to significant developments for DELICAT Laser (similar to WALES (Wirth et al, 2009)) and AEOLUS laser (even though, in this case, the difficulty also involved the space environment (Mondin et al, 2017)). In this regard, fiber laser systems can lead to better performances for on-board direct detection wind lidar.…”
Section: Introductionmentioning
confidence: 99%
“…This type of laser has the disadvantage of being sensitive to vibrations due to the number of free space optics and the presence of piezo-monitored optics to maintain the laser cavity adapted to the injected wavelength. These challenges have led to significant developments for DELICAT Laser (similar to WALES (Wirth et al, 2009)) and AEOLUS laser (even though, in this case, the difficulty also involved the space environment (Mondin et al, 2017)). In this regard, fiber laser systems can lead to better performances for on-board direct detection wind lidar.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, it has been shown that laser-induced contamination (LIC) acts as an absorber on the surface of optics, leading to lower laser damage thresholds (LDT's) and losses in transmission and reflection. For both spacebound [1] [2] and ground-based [3] systems, users and integrators of UV and/or femtosecond [4] optics must plan carefully to avoid LIC.…”
Section: Introductionmentioning
confidence: 99%